Analisis Mural Karya Arnis Muhammad Ditinjau Dari Segi Fungsi dan Gaya - Alpiza Simah Budi; Daulat Saragi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to describe the function and style of the mural by Arnis Muhammad. Mural as art in public space, which means that the space for movement and the target audience for the audience and audience is the general public. As a two-dimensional work of art, mural is also inseparable from style. Visually, the style in a work of art is the selection of objects, techniques, colors, and environmental conditions, time, era, and environmental conditions in which an artist creates his work. The population in this research is that all of Arnis Muhammad's mural works for the 2017-2019 period are 51 works. In this study the authors took samples using purposive sampling technique. The reason for taking samples is the number of mural works that still exist and are still intact. There are 10 mural works in the research location. In this case, the writer examines these mural works based on their function and style. The method used in this research is descriptive qualitative method. The function of the mural by Arnis Muhammad is a personal function as a reflection of the resonance of the environment in which he lives. Social function, as a form of concern for the environment and the surrounding community in everyday life. Physical function, as an aesthetic value enhancer and the various ways the general public use it. Arnis Muhammad's murals tend to have a surreal and decorative style.